STUDI PENGARUH BAHAN TAMBAHAN PADA POLA PUNCAK KROMATOGRAM TABLET PARASETAMOL DENGAN TLC-SPEKTROFOTODENSITOMETRI UNTUK DRUG PROFILING - Prayoga, Kadek Joni; Laksmiani, Ni Putu Linda; Widjaja, I Nengah Kadjeng (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2015)
The study of chromatogram peak pattern by influence of excipient in paracetamol tablet with TLC- Spectrophotodensitometry method for drug profiling has been done. Sample (6 kind of paracetamol tablets from different factory) and reference compounds were analyzed with TB (cyclohexane : toluene: diethylamine = 75:15:10) and TAEA (toluene : acetone : ethanol: ammonia = 45:45:7:3) as mobile phase and Al-TLC Si 60 G F254 as stationary phase. The initial step was non analyte peak reduction on Al-TLC plate with washing method, drying time and temperature variation. Sample was extracted with 1 ml chloroform and Na2CO3 buffer pH 10 and spotted on AL-TLC plate. First, sample extract from same factory was spotted on one plate, continued by sample extract from 6 different factories on one plate which is replicated five fold on each plate that different. Plate was eluted and scanned at 210 nm. Chromatogram was analyzed by cosine and cluster function. C95 value that was calculated from sample was used as a parameter to determine the influence of excipient toward chromatogram peak pattern. The result of this research showed that each tablet from same factory gave C95 value near 100 if calculated with cosine function (96 - 98,7 for TB and 78 - 83 for TAEA), whereas if all tablets from 6 different factories was used, the excipient from each tablet will give C95 value alteration (63 for TB and 68 for TAEA). Cluster analysis will divide sample into 3 different groups for TB and 1 group for TAEA.